Chitinolytic and Antagonistic Activity of Streptomyces Isolated from Fadama Soil against Phytopathogenic Fungi - Aminu Argungu Umar,; Aminu Bandam Hussaini,; Jibril Yahayya,; Ibrahim Sani,; Habiba Aminu, (Tropical Life Sciences Research, 2021)
Chitinases which degrade chitin have attracted attention as biological antifungal agents. The purpose of this study is to isolate Streptomyces from Fadama soil and assess its chitinolytic and antagonist potential against phytopathogenic fungi for application as biocontrol agent. Streptomyces were isolated from Fadama soil. The selected isolate CT02 exhibited chitinolytic characteristics. Chitinase production was performed under different temperatures, pH and varying incubation period. The highest chitinase production by CT02 isolate was observed after five days of cultivation. The highest chitinase activity was observed at 35°C and pH 7. The crude extracellular enzyme exhibited a specific activity of 4.20 U/?g whereas partially purified extracellular enzyme exhibited a specific activity of 6.19 U/?g with purification fold of 1.47. The selected isolate CT02 and its extracellular crude chitinase showed in vitro antifungal antagonist potential by inhibiting the growth of Aspergillus niger and Aspergillus oryzae. This indicates that Streptomyces derived chitinases are potential biocontrol agents against phytopathogenic fungi.